CREDIT-MODULE SYSTEM: FEATURES AND OPPORTUNITIES - Ishankhadjaeva Feruza Abduboriyevna (PT. Antis International Publisher, 2024)
This article is about the currently developing credit module system. It is about adapting the education system in our country to the world system.